2011
DOI: 10.1002/poc.1900
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic investigation on carbamate formation from the reaction of carbon dioxide with amino acids in homogeneous aqueous solution

Abstract: The kinetics of carbamate formation from the reaction of carbon dioxide with a-amino acids in D 2 O was first investigated by means of nuclear magnetic resonance spectroscopy. Potassium carbonate was used as the CO 2 source. For each amino acid, the maximum carbamate yield, the apparent rate constant for the carbamate formation k app , and the rate constants for the formation k 1 and the breakdown k À1 of the carbamate were estimated. Plots of log k 1 or log k À1 versus pK a of amino acids indicated that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…For TC-AMP formation catalyzed by YrdC, L -Thr needs to form a carbamate ( N -carboxy- L -Thr), followed by adenylation 32 . It is known that amino acids form carbamates at high concentration of bicarbonate or CO 2 at alkaline pH non-enzymatically 56 . The high Km value of bicarbonate for TC-AMP and t 6 A37 formation can be explained by the carbamate formation of L -Thr at the initial step of the reaction.…”
Section: Discussionmentioning
confidence: 99%
“…For TC-AMP formation catalyzed by YrdC, L -Thr needs to form a carbamate ( N -carboxy- L -Thr), followed by adenylation 32 . It is known that amino acids form carbamates at high concentration of bicarbonate or CO 2 at alkaline pH non-enzymatically 56 . The high Km value of bicarbonate for TC-AMP and t 6 A37 formation can be explained by the carbamate formation of L -Thr at the initial step of the reaction.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] The latter mechanism is commonly used to explain CO2 reaction with amino acids. 20,22,23 In this proposed reaction pathway In solution-based reactions, it has been reported that carbamic acids of amines and lysine peptide are selectively generated in polar aprotic solvents. 44,20 For our experiments, using LAG conditions of solvents such as DMSO and DCM led only to the formation of ammonium carbamates of L-lysine as indicated by 13 C NMR spectra ( Figure S6).…”
Section: Mechanismmentioning
confidence: 99%
“…20,22,23 In this proposed reaction pathway In solution-based reactions, it has been reported that carbamic acids of amines and lysine peptide are selectively generated in polar aprotic solvents. 44,20 For our experiments, using LAG conditions of solvents such as DMSO and DCM led only to the formation of ammonium carbamates of L-lysine as indicated by 13 C NMR spectra ( Figure S6). The latter result can be rationalized by the poor solubility of L-lysine in the organic solvents taking into account that the previously reported experiments were performed on -amino acids completely solubilized in organic solvents.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…4e). However, due to the steric hindrance of the additional methyl group (Yamamoto et al 2012), the β-amine is unfavorable; instead, the α-carbamate is favored due to the presence of the electron-withdrawing group (α-carboxylic group), promoting the formation of the C-N bond with either CO 2 or HCO 3 − .…”
Section: Chemistrymentioning
confidence: 99%